A Novel Targeted Nanoparticle for Traumatic Brain Injury Treatment: Combined Effect of ROS Depletion and Calcium Overload Inhibition. Issue 11 (17th February 2022) - Han, Zhengzhong; Han, Yuhan; Huang, Xuyang; Ma, Hongwei; Zhang, Xuefeng; Song, Jingyuan; Dong, Jun; Li, Shanshan; Yu, Rutong; Liu, Hongmei
Abstract: Survival after severe traumatic brain injury (TBI) depends on minimizing or avoiding secondary insults to the brain. Overproduction of reactive oxygen species (ROS) and Ca 2+ influx at the damaged site are the key factors that cause secondary injury upon TBI. Herein, a TBI‐targeted lipid covered radical scavenger nanoparticle is developed to deliver nimodipine (Np) (CL‐PPS/Np), in order to inhibit Ca 2+ influx in neurons by Np and to scavenge ROS in the brain trauma microenvironment by poly(propylene sulfide)60 (PPS60 ) and thus prevent TBI‐associated secondary injury. In post‐TBI models, CL‐PPS/Np effectively accumulates into the wound cavity and prolongs the time of systemic circulation of Np. CL‐PPS/Np can markedly protect the integrity of blood‐brain barrier, prevent brain edema, reduce cell death and inflammatory responses, and promote functional recovery after TBI. These findings may provide a new therapy for TBI to prevent the spread of the secondary injury. Abstract : A lipid covered poly(propylene sulfide) (PPS) is tailored as nimodipine (Np) carrier (CL‐PPS/Np) target to traumatic brain injury (TBI) site through a modified cysteine‐alanine‐glutamine‐lysine (CAQK) peptide, which can realize the combined therapy for TBI by scavenging reactive oxygen species and inhibiting calcium overload. CL‐PPS/Np may be a breakthrough in biomaterials design and addresses an unmet clinical need.